A re-look at the biochemical strategies to enhance butanol production. (November 2016) - Maiti, Sampa; Gallastegui, Gorka; Sarma, Saurabh Jyoti; Brar, Satinder Kaur; Le Bihan, Yann; Drogui, Patrick; Buelna, Gerardo; Verma, Mausam
Abstract: Butanol produced from renewable feedstock is defined as an emerging biofuel and biochemical. Research efforts made during the last three decades on biochemical production of butanol via conventional ABE (acetone-ethanol-butanol) fermentation has tried to bring biobutanol close to competition with petrobutanol. However, each new effort of development has been often countered by new challenges, confining biobutanol production mostly to the laboratory scale. This review provides a systematic, comparative analysis of different steps in biochemical production of butanol and identifies the counteractive aspects and challenges to overcome. A special emphasis is given on process inhibitors, applied detoxification techniques, chemical supplements and research & development in industry in order to enhance and update ABE fermentation and make it cost effective. Biobutanol future lies in utilization of inexpensive cellulose enriched lignocellulosic hydrolysates and hyper-butanol producing bacteria, combined with specific detoxification techniques and followed by efficient continuous fermentation technologies together with in situ product recovery. Highlights: Biobutanol production from lignocellulosic material is a promising process. Effect of microbial inhibitors and detoxification process to enhance production. Chemical supplement, hybrid technology of separation to enhance production. Key limiting factors and workable solution to enhance production. Recent update in commercialization of biobutanol.